Comparative analysis of the cranial osteology and evolutionary traits of micrastur gilvicollis, micrastur ruficollis and micrastur semitorquatus (aves: falconiformes) - Guzzi, Anderson; Santos, Francisco C. V.; Ferreira, Guilherme J. B. C.; Donatelli, Reginaldo José [UNESP] (My University, 2014)
The cranial osteology of Micrastur gilvicollis (Vieillot, 1817), Micrastur ruficollis (Vieillot, 1817) and Micrastur semitorquatus (Vieillot, 1817) is comparatively and meticulously described to characterize each of the species and to determine which traits the species have in common and which are distinct. These traits will be used a posteriori for phylogenetic analysis. Our results indicate that M. gilvicollis and M. ruficollis are closely related, as they share a large number of traits, including a lacrimal bone with a distal portion that is approximately half as long as the proximal portion and a parasphenoid rostrum that covers 50% of the distance between the occipital condyle and pterygoid. Similarly, M. gilvicollis and M. semitorquatus both have a partially fused craniofacial flexion zone. In both M. ruficollis and M. semitorquatus, the symphyseal region of the mandible is 1/5 the total length of the mandible. The diagnostic traits for each of these species are as follows: a) in M. gilvicollis, the interorbital distance is 1/3 the length of the parietal, and the zygomatic process stretches 1/5 of the distance from the orbital arch to the jugal arch; b) in M. ruficollis, the interorbital distance is 2/5 of the length of the parietal and the zygomatic process extends 1/4 of the distance from the orbital arch to the jugal arch; and c) in M. semitorquatus, the interorbital distance is 3/7 the length of the parietal and the distal portion of the lacrimal is 1/3 the length of the proximal portion. Among the three species, M. gilvicolis and M. ruficollis share the most traits, which leads us to infer that these species are more closely related to one another than they are to M. semitorquatus. Phylogenetic analysis performed a posteriori may confirm the relationship between these three species.

A osteologia craniana de Micrastur gilvicollis (Vieillot, 1817) Micrastur ruficollis (Vieillot, 1817) e Micrastur semitorquatus (Vieillot, 1817) é descrita de forma detalhada e comparada visando caracterizar cada uma das espécies e interpretar os caracteres comuns e particulares que serão utilizados a posteriori em uma análise filogenética. Os resultados evidenciaram uma proximidade entre as duas primeiras espécies por compartilharem um grande número de caracteres, tais como a parte distal do lacrimal com cerca de 1/2 da proximal e o rostro paraesfenóide alcançar 50% da distância do côndilo occipital e o pés pterigoide. Por outro lado, M. gilvicollis e M. semitorquatus compartilham a condição parcialmente fundida da zona flexória craniofacial. Entre M. ruficollis e M. semitorquatus a parte sinfisial da mandíbula ocupa 1/5 do comprimento total da mandíbula. Os caracteres diagnósticos cada uma dessas espécies são: a) em M. gilvicollis a largura interorbital é 1/3 da parietal e o processo zigomático atinge 1/5 da distância a partir do arco da órbita à barra jugal; b) em M. ruficollis a largura interorbital tem 2/5 da parietal e o processo zigomático atinge 1/4 da distância a partir do arco da órbita à barra jugal; c) em M. semitorquatus a largura interorbital é 3/7 da parietal e a parte distal do lacrimal tem 1/3 da largura da proximal. Micrastur gilvicolis e M. ruficollis compartilham um maior número de caracteres, o que permite inferir que tais espécies estão mais próximas entre si quando comparadas a M. semitorquatus. Uma análise filogenética a posteriori poderá ou não confirmar essa relação entre essas três espécies.
Keywords: Anatomia; Crânio; Falconidae; Anatomy; Skull; Falconidae